Meningkatkan Kognitif Anak Usia Dini melalui Media Flashcard - Novi Tri Utami (STAI Auliaurrasyidin Tembilahan, 2023)
One of the cognitive abilities of early childhood (AUD) is symbolic thinking, which includes the ability to know, mention, and use the concept of numbers. The cognitive abilities of students of RA Sabilil Huda Sanglar, Reteh have not developed optimally. This study aims at improving students’ cognitive abilities through flashcard media. It is a Class Action Research (CAR), which was carried out in group B RA Sabilil Huda Sanglar, Reteh. This was designed for two cycles, where each cycle consisted of three meetings (two meetings for treatment, and one meeting for tests). Data were collected using observations, tests, and field notes. They were then subsequently analyzed descriptively. Based on the data, it is known that students’ cognitive abilities are at an average of 36.25 (45.31%) with the Start to Develop (SD) category in the pre-cycle, 56 (70%) with the Very Well Developed (VWD) category in the cycle I, and 75.6 (94%) with the Very Well Developed (VWD) category in the cycle II. Thus, the use of flashcard media can improve the cognitive abilities of group B students of RA Sabilil Huda Sanglar, Reteh.